THE REPRESETATION OF THE NURULS AS SOCIAL CONSTRUCTION OF HIJAB-WEAARING WOMEN IN SOCIAL MEDIA - Bunaiya Nawal Salwa; Ade Khoirunnisa; Nina Farlina (2025)
This study aims to understand how representation of The Nurul as a social construction that reflects the dynamics between religious identity, gender and modernity in Indonesian society. The term the Nurul was first introduced by content creator Halda Rianta in the PodHub podcast in January 2024, and went viral on social media. The Nurul is often associated with behaviors such as dancing in cafes, enjoying fast food such as seblak, riding motorbikes and wearing casual clothes such as knitted sweaters and Korean-style wire glasses. This study uses a qualitative approach with content analysis and the theory of representation of Stuart Hall reveals how this stereotype influences public perception of women who wear the hijab and how they associate their identities in the digital space. The result, this study is a representation of the complexity of the identity of women who wear the hijab who try to balance religious values ​​and the demands of a modern lifestyle. This study also investigates the impact of social media on views and behavioral judgments, specifically in cultural and religious settings.